2023
DOI: 10.3746/pnf.2023.28.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Production of Dipeptidyl Peptidase-IV Inhibitory Peptides from Germinated Jack Bean [Canavalia ensiformis (L.) DC.] Flour

Abstract: An alternate plant-based protein, jack bean sprout, was explored as a source of bioactive peptides. Germination to increase dipeptidyl peptidase-IV (DPP-IV) inhibitory peptide in jack bean sprout flour has yet to be reported. Therefore, this study aimed to investigate the optimal condition to maximize the content of bioactive peptides with maximum DPP-IV inhibitory activity. The relationship between germination and DPP-IV inhibitory activity was determined by analyzing the proteolytic activity, percentage of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…From our hypothesis, hemp seed peptides might exhibit antidiabetic properties comparable to those of edible plant-derived peptides, as reported in previous studies. For example, short, low-molecular-weight peptides from Bambara bean (hydrolyzed by alcalase); soy, quinoa, and lupine (subjected to sequential hydrolysis with subtilisin–trypsin–flavourzyme); and jack bean (digested by pepsin–pancreatin) have been experimentally shown to possess DPPIV inhibitory properties through in vitro enzyme activity tests [ 18 , 29 , 60 , 61 ]. Currently, the idea of predicting and simulating the digestion of plant high-abundance proteins through gastrointestinal tract enzymes (pepsin, trypsin, pancreatin, and chymotrypsin) to represent the peptidome profile in the human gut after a meal has been applied to many edible plants [ 21 , 24 , 29 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From our hypothesis, hemp seed peptides might exhibit antidiabetic properties comparable to those of edible plant-derived peptides, as reported in previous studies. For example, short, low-molecular-weight peptides from Bambara bean (hydrolyzed by alcalase); soy, quinoa, and lupine (subjected to sequential hydrolysis with subtilisin–trypsin–flavourzyme); and jack bean (digested by pepsin–pancreatin) have been experimentally shown to possess DPPIV inhibitory properties through in vitro enzyme activity tests [ 18 , 29 , 60 , 61 ]. Currently, the idea of predicting and simulating the digestion of plant high-abundance proteins through gastrointestinal tract enzymes (pepsin, trypsin, pancreatin, and chymotrypsin) to represent the peptidome profile in the human gut after a meal has been applied to many edible plants [ 21 , 24 , 29 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…This approach allows for the observation of not only the availability of these bioactive peptides but also their absorption potential using the everted gut sac method [ 29 ]. Through computer-aided analysis, in silico studies employing bioinformatics approaches have identified potential antidiabetic peptides in macadamia, soybean, black bean, and hemp [ 17 , 18 , 34 , 36 , 40 , 41 ]. Together with our virtual screening and validation results, these findings suggest that hemp seed peptides could play a therapeutic role in managing diabetes through DPPIV inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation